Integrated modeling and analysis approach for design and configuration of the supply chain - Xie, Xudong. (2008)
Several challenging problems are associated with the integrated supply chain design: (1) how to build an integrated modeling and analytic approach to consider the various factors, such as decision levels and stochastic factors and so on, (2) how to establish the information and function connectivity between the sub-models in the integrated system, (3) how to model the operating mechanism of supply chain in the individual sub-model of different decision levels, and (4) what is the focus of the individual modeling stage and how to implement proposed approach in practical utilization. This research answers these questions by proposing the Integrated Analytic- Simulation Modeling and Analysis (IASMA) methodology.